the Effect Of Single Multiple Jump Training On Long Passing Results In Football Games Team Tambusai FC : Pengaruh Latihan Single Multiple Jump Terhadap Hasil Long Passing Dalam Permainan Sepak Bola Team Tambusai FC - Aleb, Alebri (Journal Of Sport Education and Training, 2024)
ABSTRACT: Nusantara soccer school 15-17 years old Malang city have a problem insoccer basic technique, it is long pass skill. The purpose of this research is to know theinfluence exercise of single multiple jump and exercise of knee tuck jump to long pass skillin Nusantara soccer school 15-17 years old Malang city.This research using experimentresearchmatching pretest-posttest comparison group design with subject 22student.Based from F count 4,70 > F table 4,35 for exercise of single multiple jump, while F count0,842 < F table 4,35 for exercise of knee tuck jump. The comparison from two excercisescan be obtained F count 12,29 > F table 4,35. Based on the research can be concludedthatexerciseofsingle multiplejump give influencebetter than excersieofkneetuckjump. Keywords:singlemultiplejump,kneetuckjump,longpass. ABSTRAK:SekolahSepakbolaNusantarausia15-17tahunKotaMalangmemilikimasalahpadateknikdasarsepakbolayaituketerampilanlongpass.Penelitianinibertujuan untuk mengetahui pengaruh latihan single multiple jump dan knee tuck jumpterhadap keterampilan long pass pada siswa Sekolah Sepakbola Nusantara usia 15-17tahunKotaMalang.Metodeyangdigunakandalampenelitianiniadalahpenelitianeksperimen matching pretest-posttest comparison group design dengan jumlah subjek 22siswa. Berdasarkan hasil perhitungan F hitung 4,70 > F tabel 4,35 untuk latihan singlemultiplejump,sedangkanlatihankneetuckjumpFhitung0,842<Ftabel4,35.PerbandingandarikeduakelompoklatihandiperolehFhitung12,29>Ftabel4,35,sehingga dapat disimpulkan latihan single multiple jump memberikan pengaruh yang lebihbaikdaripadalatihankneetuckjump.